Na pescaria direcionada ao Ariacó no município Salinópolis/Pará, o incremento tecnológico é proporcional à rentabilidade? - SENA, Lenilson de Souza de (2024)
Ariacó Lutjanus synagris fishing by the fleet based in the municipality of Salinópolis, State of Pará, takes place using small vessels with sail or motor propulsion. This characteristic is accompanied by different forms of conservation, demand for inputs and division of labor on board. This study aimed to analyze whether the technological increase is proportional to profitability in this fishery. From May to December 2022, three categories were evaluated in terms of technical and economic aspects: 1) sail canoe equipped with isothermal expanded polystyrene boxes; 2) canoe with outboard motor equipped with zinc isothermal boxes; and 3) inboard engine boat with injected polyurethane isothermal urn, radio and GPS. The boat crews are made up of 5 people, among whom there is a simple division of functions, with emphasis only on the boss, who coordinates the driving of the boat to the fishing points. In non-motorized vessels, however, the person in charge is the bowman, who commands all the fishing. The others take turns fishing, storing fish and preparing food. This study took place in the northeast mesoregion of the state of Pará, 200 km from the capital, Belém. Observing the commercialization of the same, and accompanying fauna composed of several species, whose purpose is the municipalities of Bragança/PA and São João de Pirabas/PA. This fishing system in the municipality of Salinópolis is a pioneer in scientific study, as there is no literature on its approach, as well as the investment required and its profitability.